Penggunaan Pendekatan System Thinking dalam Penyusunan Policy Paper Penurunan Angka Kawin Anak di Jepara - Mayadina Rohmi Musfiroh (Isti`dal : Jurnal Studi Hukum Islam, 2022)
The excessive rate of child marriage has a systemic impact on the future of children and the quality of family life. This phenomenon is shown by the number of submissions for marriage dispensation recommendations at the Religious Courts in recent years. In 2021, the main factors behind the application for a recommendation for dispensation for underage marriages are due to pregnancy (157 applications or 40.7%), avoiding adultery (155 applications or 40.2%), getting pregnant (44 applications or 11.4%) and had had sex (29 submissions or 7.5%). Of the 385 applications for a marriage dispensation recommendation, only 246 applications (63.7%) were granted by the Religious Courts. Child marriage will have a systemic impact, including decreasing the quality of life of women, children and families, increasing poverty rates and vulnerability to families. This activity aims to conduct an in-depth analysis of the factors that cause child marriage and formulate strategies and policies to reduce child marriage rates in Jepara, using the multi-stakeholder Focus Group Discussion method and the iceberg analysis model and U theory. trends, structures, mental models and sources that lead to high child marriages as well as the formulation of new mental models, program designs and policies to reduce child marriage rates in a more sustainable, comprehensive and integrated manner.